Big Data in Context: A Narrative Review of Opportunities, Barriers, and Global Perspectives - Achaddiah, Bella Noer; Safri (Novatio : Journal of Management Technology and Innovation, 2024)
This narrative review examines the transformative role of big data in organizational performance, predictive analytics, and smart manufacturing, while highlighting disparities in adoption between developed and developing economies. Literature was collected from major databases (Scopus, Web of Science, PubMed, and Google Scholar) using rigorous criteria to ensure methodological validity. Findings reveal that big data improves decision-making, efficiency, and risk management, with digital twin technologies enhancing reliability in manufacturing. However, barriers remain, including infrastructure gaps, skill shortages, resistance to change, and data governance challenges—especially among SMEs and rural communities. The review underscores the need for targeted policy interventions and cross-sector collaborations to close these gaps. Its unique contribution lies in synthesizing global disparities and offering integrative strategies for inclusive, sustainable big data adoption.